Bacteriological Profile and Antibiotic Resistance Pattern in Children with Urinary Tract Infection in a Tertiary Care Hospital (Sir Salimullah Medical College Journal, 2022)
Introduction: Urinary tract infection (UTI) is one of the most common bacterial infections seen in children. The knowledge of bacterial causes of UTIs and their antimicrobial resistance patterns may help clinicians in choosing the appropriate antimicrobials.Objectives: The present study was designed to find out the bacteriological profile of urinary tract infection and their antibiotic resistance pattern in children.Methodology: A cross sectional study was done in the department of Microbiology, Sir Salimullah Medical College from January to December 2019. Midstream urine samples were collected from clinically suspected cases of UTI in the age group of 0 to 18 years from various indoor and outdoor patients of Mitford hospital for this study.Results: Out of 2763 cases, 363 were culture positives, where females were 202(55.65%) with highest number of cases within the age group of 0 to 4 years (63.36%). Most common isolate identified was Escherisia coli, followed by Pseudomonas, Proteus, Morganella and only Gram positive bacteria was S. aureus. Organisms show highest resistance to Amoxiclav, Cefixime, Cotrimoxazole, Ciprofloxacin and highest sensitivity to Amikacin.Conclusion: This study revealed that UTI was more common in female & under five children. Escherichia coli were the commonest isolated organism and all isolates show high resistance to common antimicrobial agents.Sir Salimullah Med Coll J 2021; 29(2): 112-116